PENGARUH IMPLEMENTASI KEBIJAKAN PERUBAHAN STATUS DESA MENJADI KELURAHAN TERHADAP PRODUKTIVITAS USAHA PEREKONOMIAN MASYARAKAT KELURAHAN JAMPANGKULON - Purwanto (STISIP Widyapuri Mandiri, 2022)
This study aims to determine: (1) the implementation of the policy of changing the status of a village to a sub-district, (2) the productivity of the community's economic business, and (3) the influence of the implementation of the policy of changing the status of a village to a village on the productivity of the community's economic business in the Jampangkulon Village. The population of this research is all economic business actors in Jampangkulon Village, totaling 782 people, with a total sample of 89 people taken using the Proportionate Stratified Random Sampling technique. The results of the calculation of descriptive analysis show that the average score of the Variable Policy Implementation Changes in Village Status into Kelurahan is 3.47 or 69.40% of the ideal value and is included in the good category, while the Productivity of Community Economic Enterprises is 3.65 or 73.00 % of the ideal value and included in the good category. The results of statistical analysis obtained the price of rXY = 0.428 which is included in the criteria is quite strong. With a significance value (2-tailed) 0.000 <0.05, so it can be concluded that the Implementation of the Policy on Changing the Status of a Village to a Village has a positive and significant effect on the Productivity of Community Economic Enterprises. The coefficient of determination (KD) is 0.1832, which means 18.32% of the Community Economic Business Productivity variable (Y) can be explained by the Variable of Policy Implementation to Change Village Status to Kelurahan (X), and the rest is determined by other factors. While the linear regression equation model obtained is Y = 23.993 + 0.483X. Therefore, to increase the productivity of the community's economic business, it is recommended to increase the efficiency and effectiveness of the Policy Implementation to Change the Status of Villages to Villages.